2015
DOI: 10.2334/josnusd.57.31
|View full text |Cite
|
Sign up to set email alerts
|

Associations of interleukin (IL)-1β, IL-1 receptor antagonist, and IL-10 with dental caries

Abstract: Streptococcus mutans is important in dental caries. Although the role of cytokines in the pathogenesis of dental caries is not clear, components of S. mutans were found to stimulate production of pro-inflammatory cytokines. We examined the associations of interleukin (IL)-1β, IL-1 receptor antagonist (IL-1ra), and IL-10 with dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…Proteins such as lysozymes, interleukins, mucins, and lactotransferrin (LTF) can promote cell aggregation, inhibition, and/or bacterial adherence. 4,5,6,7 Other proteins, such as beta defensins, have…”
mentioning
confidence: 99%
“…Proteins such as lysozymes, interleukins, mucins, and lactotransferrin (LTF) can promote cell aggregation, inhibition, and/or bacterial adherence. 4,5,6,7 Other proteins, such as beta defensins, have…”
mentioning
confidence: 99%
“…Prso et al reported that patients with periapical root lesions had higher IL levels than the control group (28). There are studies indicating that there is a relationship between tooth decay and cytokines and there are other studies that indicate otherwise (4,29).…”
Section: Resultsmentioning
confidence: 99%
“…Even though the interactions between pathological (acidogenic bacteria, fermentable carbohydrates) and protective factors (saliva components: proteins, fluoride, calcium, phosphate), are complex, the disease can easily be prevented if the dynamic balance between the protective and pathological factors can be kept in equilibrium (3,5,6). Mutans streptococci, and Lactobacilli are the two important caries associated acidogenic bacteria of dental caries (1,4). An increase in the numbers of S. Mutans in saliva is associated with caries initiation where as an increase in the number of lactobacilli indicates progressed lesions of caries (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations